Customer Purchase Intention For Sanitary Napkins On E-Commerce Platforms In Jakarta Area - Andita, Matthew; Prayitno, Sentot Basuki (SEAN Institute, 2024)
Softex has been on the top of mind for Indonesian consumers for sanitary pads for the last decade. The study aims to investigate how purchase intention can be affected by brand awareness, electronic word-of-mouth, and product packaging design indicators towards a brand on the online marketplace, in this case, the brand is Kimberly-Clark Softex. The independent variables of the study are brand awareness, electronic word-of-mouth, and product packaging design; and the dependent variable of the study is online purchase intention. By analyzing indicator factors above, the study aims to see how brand awareness, electronic word-of-mouth and product packaging design variables may affect purchase intention on the online marketplace. Moreover, the study also seeks to aim on the strongest indicators out of the variables on which has the strongest effect towards consumer’s purchase intention of Softex sanitary napkin products on Indonesian e-commerce. The study uses quantitative methods and questionnaires will be utilized for the data collection. Respondents in this study selected by using non-probability sampling. Based on the findings of the study, the indicators which are in the scope of the study which are brand awareness, electronic word-of-mouth, and product packaging design shows significance and positive influence towards purchase intention of KC-Softex on the e-commerce and highest significant impact is brand awareness.